Polymorphism of Growth Hormone (GH) Gene in Lakor Goat from Lakor Island of Southwest Maluku Regency - Rony Marsyal Kunda; Slamet Diah Volkandari; Maman Rumanta; Pieter Kakisina (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
Lakor goat survive in Lakor island in Southwest Maluku with high temperature and limited water. Growth trait in goat is interest to explore cause related with economic trait that encoded by growth hormone (GH) gene. The aim of this study was identify of polymorphism GH gene of Lakor goat in Lakor island. A total of 63 samples were collected from three locations (village) i.e Ketti Letpey (18), Werwawan-Yamluli (26), and Letoda (19). DNA was extracted from hair follicles. A 422 bp specific DNA fragment was successfully amplified and genotyped by PCR-RFLP method using HaeIII enzyme. Results showed that polymorphism was found with two variant of genotypes (AA and AB) and two alleles (A and B). AB genotype was dominant in all of populations (93.7%) with A and B alleles were 0.53 and 0.47, respectively. Heterozygosity observed and expected value reached 0.502 and 0.498, respectively while Polymorphic Information Content was in moderate values (0.374). All of populations were in disequilibrium genetic. It maybe caused limited buck and nonrandom mating in population that effect of low genetic variation. Inbreeding study are needed to explore it. The introgression of bucks from other families in several locations within Lakor island can be an alternative solution to increase the genetic diversity of the lakor goat population.